HUBUNGAN MATRIXMETALLOPROTEINASES-9 DAN THROMBOSPONDIN-1 DENGAN TEKANAN DARAH PADA ANAKDENGAN RIWAYAT BERAT LAHIR RENDAH - Umboh, Adrian; Wilar, Rocky; Bernadus, Janno B. B. (JKK (Jurnal Kedokteran Klinik), 2019)
AbstractDisorders of endothelial function that occur in low-weight infants can result in increased levels of Metallo proteinases-9 (MMP-9) and Thrombospondin-1 (TSP-1) and are associated with increased blood pressure. MMP-9 is a family of endopeptidaseszinc-dependent that is responsible for tissue remodeling, both physiological and pathophysiological. The purpose of this study was to see the relationship between MMP-9 and TSP-1 with birth weight and blood pressure in children with a history of low birth weight. This study was a correlational observational analytic with cross sectional approach, namely by looking at the relationship between MMP-9 and TSP-1 levels with birth weight and blood pressure. This research was conducted from April to October 2018 at RSUP Prof. Dr. R. D Kandou Manado, North Sulawesi in children aged 7-9 years with a history of low birth weight. Blood pressure is measured by sfigmano meter. Inclusion criteria are children in good health with good nutritional status, having birth weight records in medical records, and parents willing to sign informed consent. Exclusion criteria were children in sick condition, taking drugs in 2 weeks before the study, obesity and suffering from kidney disease. MMP-9 levels measured by the enzyme-linked Quantikine Human MMP-9 method and TSP-1 levels were measured by the R & D System human thrombospondin-1 immunosorbent assay method.Keywords: Metallo proteinases-9 Matrix, Thrombospondin-1, low birth weight, blood pressure AbstrakGangguan fungsi endotel yang terjadi pada bayi berat lahi rrendah dapat mengakibatkan  terjadinya  meningkatnya  kadar  Matrix  Metallo  proteinases-9 (MMP-9) dan Thrombospondin-1(TSP-1) serta berhubungan dengan   peningkatan tekanan  darah.  MMP-9  adalah keluarga dari endopeptidaseszinc-dependent  yang bertanggungjawab untuk remodeling jaringan, baik fisiologis maupun patofisiologis. Tujuan penelitian ini untuk Melihat hubungan MMP-9 danTSP-1 dengan berat badan lahir dan tekanan darah pada anak dengan riwayat berat lahir rendah. Penelitian ini bersifat observasional analitik korelatif dengan pendekatan potong lintang yaitu dengan melihat hubungan kadar MMP-9 dan TSP- 1 dengasn berat lahir dan tekanan darah. Penelitian ini dilakukan mulai bulan April sampai  Oktober  2018  pada RSUP Prof. Dr. R. D Kandou Manado, Sulawesi Utara pada anak usia7-9 tahun dengan riwayat  berat  lahir rendah. Tekanan darah diukur dengan sfigmano meter. Kriteria inklusi adalah anak dalam keadaan sehat dengan status gizi baik, memiliki catatan berat lahir dalam rekam medis, dan orang tua bersedia untuk menanda tangani informed consent. Kriteria eksklusi adalah anak dalam kondisi sakit, mengkonsumsi obat- obatan dalam 2 minggu sebelum penelitian, obesitas dan menderita penyakit ginjal. Kadar MMP-9 diukur dengan metode Human MMP-9 enzyme-linked Quantikine dan kadar TSP-1   diukur   dengan   metode   R&D   System   human   thrombospondin- 1immunosorbent assay kit.Katakunci: Matrix Metallo proteinases-9,Thrombospondin-1, berat lahir rendah,tekanan darah